Time since contact influences DNA profiling success of cartridges and fired cartridge casings. (November 2022) - Winnepenninckx, Astrid; Verhoeven, Elke; Vermeulen, Steve; Jeurissen, Bert; Borgers, Erwin; Bekaert, Bram
Abstract: Forensic DNA analysis of cartridges and fired cartridge casings remains challenging, possibly due to the heat and pressure generated during firing of the weapon as well as metal ions from the casings that have been suggested to initiate DNA degradation and inhibit PCR during the DNA profiling process. Even though recently developed DNA recovery protocols have shown to significantly improve DNA yields and DNA profile success rates no information is available on whether the time interval between contact and the DNA recovery process has an influence on these outcomes. In the current study 40 cartridges and 40 fired cartridge casings were left untreated for 24 h or 1 week after which the rinse-and-swab technique was used to collect DNA. Higher DNA yields and higher DNA profile success rates were obtained from cartridges compared to fired cartridge casings. The same general observation was made when cartridges and fired cartridge casings were processed after 24 h compared to after 1 week. In addition, DNA profiles suitable for comparison could still be generated from samples when real-time PCR quantification indicated DNA concentrations < 0.001 ng/ μ l, suggesting that quantification results may not be reliable when assessing the presence of DNA on such items. In conclusion, the results indicate that cartridges and fired cartridge casings should be processed for DNA profiling as soon as possible and that DNA quantification results should be interpreted with caution as DNA profiles suitable for comparison could be missed. Highlights: Swabs with their containers can be used to safely collect and transport fired 9▒mm cartridge casings DNA yield and the quality of DNA profiles is significantly influenced by time after manipulation of cartridges and fired cartridge casings Lower DNA yields and lower quality DNA profiles were obtained from fired cartridge casings DNA profiles should always be produced even if quantification indicates a DNA concentration of < 0.001 ng/μl is present